PERAN OTORITAS SYARIAH DALAM HILIRISASI EKONOMI MELALUI PRODUK FINTECH SYARIAH - Soraya Ayumara; Aan Zulyanto; Marini Marini (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Sharia fintech has become a strategic instrument in the downstream of the Indonesian economy, especially in distributing financing to Micro, Small, and Medium Enterprises (MSMEs) that have been experiencing limited access to formal capital. This article aims to analyze the role of sharia authorities, namely the National Sharia Council-Indonesian Ulema Council (DSN-MUI) and the Sharia Supervisory Council (DPS), in facilitating and supervising economic downstream through sharia fintech products using a qualitative approach with a literature study method on sharia economic literature, Financial Services Authority (OJK) regulations, DSN-MUI fatwas, and empirical research for the 2020-2025 period on fintech sharia and MSME financing. The results of the study show that DSN-MUI plays a role as a normative framework through Fatwa No. 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles which is the operational basis of sharia fintech, while DPS functions as a supervisor, advisor, and reviewer which ensures sharia compliance at the operational level of the platform (The Role of DPS, 2022; Implementation of DSN-MUI Fatwa, 2024). Sharia fintech has been proven to expand financial inclusion and increase access to MSME financing through mudharabah, musyarakah, and halal crowdfunding contracts that are effective in improving economic justice, with financing growth of 35% for the 2020-2023 period and more than 50% of beneficiaries coming from MSMEs (Financial Services Authority, 2023; Munawar, 2025). The economic downstream process is facilitated through a feasibility assessment based on digital data, quick access without physical collateral, and Islamic financial literacy assistance that increases the managerial capacity of business actors (The Role of Sharia Fintech MSMEs, 2024; MSME Financial Transformation, 2025). However, implementation faces challenges in the form of limited DPS capacity that understands technology, digital literacy gap for MSME actors, and the need for regulatory harmonization between the OJK, DSN-MUI, and the Ministry of Cooperatives (The Role of DPS Compliance, 2025). This article concludes that strengthening sharia authorities requires three integrative strategies: improving the competence of DPS through financial technology training and sharia maqashid, the development of RegTech and SupTech for automated compliance audits, and strengthening collaboration between DSN-MUI, OJK, and industry players to ensure fintech Sharia plays an optimal role in the downstream of an inclusive, just, and sustainable economy according to the principle of maslahah. Keywords: sharia authority, DSN-MUI, DPS, Sharia Fintech , Economic Downstreaming, MSMEs, financial inclusion